Adjusting the Movements of the Robotic Platform Through Inverse Kinematics - Nevliudov, I. Sh.; Gurin, D.; Yevsieiev, V. (My University, 2025)
The paper presents an approach to the development of a control system for a quadruped robotic platform using inverse kinematics. The solution enables accurate movement of the robot's legs to achieve stable motion and balancing under uncertain terrain conditions. The kinematic model is calculated using FreeCAD tools and implemented in a control code through the transformation of joint angles into PWM signals for servo drives. A simulation model in MATLAB Simulink was created to test the stabilization algorithm. The obtained results demonstrate the ability of the system to correct the robot's posture and maintain balance in real time, even under significant external disturbances .
Keywords: quadruped robot; inverse kinematics; PID control; MATLAB Simulink; robotic balance